KOMUNIKASI ORGANISASI BAGIAN LEGISLASI DALAM PENGESAHAN RAPERDA DI SEKRETARIAT DPRD KOTA PALEMBANG: ANALISIS BERDASARKAN TEORI SISTEM UMUM DI SEKRETARIAT DPRD KOTA PALEMBANG - Putri , Meytha Cahya; Ritonga, Muslimin (UNIVERSITAS STEKOM, 2025)
Organizational communication plays an important role in the management and decision-making of an institution, including in legislative institutions such as the Regional People's Representative Council (DPRD). This study aims to analyze how organizational communication that takes place in the Palembang City DPRD Secretariat can influence the process of ratifying the Raperda. In addition, this study also aims to explore ways to improve the effectiveness of communication between parties involved in the legislative process. This study applies a qualitative approach with a descriptive research type. The results of the study indicate that effective communication between superiors and subordinates, between parallel sections, and between sections with different tasks plays an important role in facilitating the legislative process.